Univerze kot pospeševalec trajnostnega razvoja - Arbeiter, Jana (Teorija in praksa, 2024)
As the largest and most interdisciplinary social science faculty in the Slovenia, and forming part of the University of Ljubljana, the Faculty of Social Sciences is an important actor for promoting realisation of the Sustainable Development Goals (SDGs), The Faculty’s mission includes all three key aspects of sustainable development: social, economic and environmental. Experts there (researchers and educators) are actively involved in international networks for the design, education and measurement of SDGs and actively participate in the monitoring and implementation of the Agenda for Sustainable Development until 2030; namely, the most ambitious global agreement ever to target sustainable development. They also transfer experiences and references from international projects in the field of global and transformative learning (SDG 4.7,) understood as a key instrument for the accomplishment of all 17 goals. The contribution presents analysis of the inclusion of the SDGs in the pedagogical, scientific and management areas of the Faculty’s operations.
Keywords: cilji trajnostnega razvoja; CTR; education; izobraževanje; sustainable development; sustainable development goals; Trajnostni razvoj; universities; univerza; Univerza v Ljubljani, Fakulteta za družbene vede